Implementasi Manajemen Mutu Terpadu dalam Pendidikan Islam: Sebuah Systematic Literatur Review tentang Resiliensi Lembaga dan Kepuasan Stakeholder - Yusnida Abila; Maftuhatul Afrah; Moch. Wildani Dwi Sulaiman; Mu’allimin Mu’allimin (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Improving the quality of education has become a crucial issue in the era of globalization, marked by increasing competition between institutions and public expectations for superior educational services. Integrated Quality Management (TQM) emerges as a strategic approach to improve the effectiveness, efficiency, and satisfaction of various educational stakeholders. This study aims to review the development of studies related to TQM implementation in education through a qualitative literature review. Data were collected from scientific articles published between 2020 and 2025 using Google Scholar and Publish or Perish with the keywords